EFFECTIVENESS OF THE PROJECT-BASED LEARNING MODEL (PJBL) IN INCREASE CREATIVITY ISLAMIC EDUCATION MATERIAL STUDENTS - Dukan Jauhari F; Imam Bukhori; Faishol Hakim (UAS PRESS, 2025)
Creativity is one of the important competencies that needs to be developed in students, especially at the elementary school level. However, in the learning practices at madrasah ibtidaiyah, the development of students' creativity is still not optimal because learning tends to be teacher-centered . This study aims to determine the effectiveness of the Project-Based Learning (PJBL) model in increasing the creativity of fifth-grade students at MI Bustanul Ulum 02 Mlokorejo. This study used a quantitative approach with an experimental research type and a One-Group Pretest–Posttest Design. The research subjects consisted of 20 fifth-grade students. The research instrument was a creativity test covering the indicators of fluency, flexibility, originality, and elaboration. The data were analyzed using the Shapiro–Wilk normality test and the paired sample t-test with the help of SPSS version 25.0. The results showed that the data were normally distributed and there was a significant difference between the students' pretest and posttest creativity scores. The significance value of the paired sample t-test was 0.000 < 0.05, indicating that the PJBL learning model was effective in improving student creativity. Creativity increases in all indicators, namely fluency, flexibility, originality, and elaboration. Thus, it can be concluded that the application of the Project-Based Learning (PBL) model is effective in increasing the creativity of fifth-grade students at MI Bustanul Ulum 02 Mlokorejo.